Rare BANF1 Alleles and Relatively Frequent EMD Alleles Including ‘Healthy Lipid’ Emerin p.D149H in the ExAC Cohort - Dharmaraj, Tejas; Guan, Youchen; Liu, Julie; Badens, Catherine; Gaborit, Benedicte; Wilson, Katherine L. (Frontiers in Cell and Developmental Biology, 2019)
Emerin (EMD) and barrier to autointegration factor 1 (BANF1) each bind A-type lamins (LMNA) as fundamental components of nuclear lamina structure. Mutations in LMNA, EMD and BANF1 are genetically linked to many tissue-specific disorders including Emery-Dreifuss muscular dystrophy and cardiomyopathy (LMNA, EMD), lipodystrophy, insulin resistance and type 2 diabetes (LMNA) and progeria (LMNA, BANF1). To explore human genetic variation in these genes, we analyzed EMD and BANF1 alleles in the Exome Aggregation Consortium (ExAC) cohort of 60,706 unrelated individuals. We identified 13 rare heterozygous BANF1 missense variants (p.T2S, p.H7Y, p.D9N, p.S22R, p.G25E, p.D55N, p.D57Y, p.L63P, p.N70T, p.K72R, p.R75W, p.R75Q, p.G79R), and one homozygous variant (p.D9H). Several variants are known (p.G25E) or predicted (e.g., p.D9H, p.D9N, p.L63P) to perturb BANF1 and warrant further study. Analysis of EMD revealed two previously identified variants associated with adult-onset cardiomyopathy (p.K37del, p.E35K) and one deemed ‘benign’ in an Emery-Dreifuss patient (p.D149H). Interestingly p.D149H was the most frequent emerin variant in ExAC, identified in 58 individuals (overall allele frequency 0.06645%), of whom 55 were East Asian (allele frequency 0.8297%). Furthermore, p.D149H associated with four ‘healthy’ traits: reduced triglycerides (-0.336; p=0.0368), reduced waist circumference (-0.321; p=0.0486), reduced cholesterol (-0.572; p=0.000346) and reduced LDL cholesterol (-0.599; p=0.000272). These traits are distinct from LMNA-associated metabolic disorders and provide the first insight that emerin influences metabolism. We also identified one novel in-frame deletion (p.F39del) and 62 novel emerin missense variants, many of which were relatively frequent and potentially disruptive including p.N91S and p.S143F (~0.041% and ~0.034% of non-Finnish Europeans, respectively), p.G156S (~0.39% of Africans), p.R204G (~0.18% of Latinx), p.R207P (~0.08% of South Asians) and p.R221L (~0.15% of Latinx). Many novel BANF1 variants are predicted to disrupt dimerization or binding to DNA, histones, emerin or A-type lamins. Many novel emerin variants are predicted to disrupt emerin filament dynamics or binding to BANF1, HDAC3, A-type lamins or other partners. These new human variants provide a foundational resource for future studies to test the molecular mechanisms of BANF1 and emerin function, and to understand the link between emerin variant p.D149H and a ‘healthy’ lipid profile.